2022
DOI: 10.31083/j.rcm2307242
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants in Patients with Atrial Fibrillation and Active Cancer

Abstract: Background: Atrial fibrillation (AF) is associated with an increased risk of heart failure, death and thromboembolism. AF is prevalent in patients with cancer. Although current guidelines suggest the application of oral anticoagulants (OACs) for thromboembolic event prevention in high-risk AF patients, owing to the high thromboembolic and bleeding risks of active-cancer patients, there is no consensus on the use of OACs in such a population. Therefore, we conducted this retrospective cohort study to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…[70] Rats injected with cardiomyocyte-derived EVs rich in HSP20 showed activation of vascular endothelial growth factor receptor 2 and Akt signaling, a decrease in tumor necrosis factor and IL-1, an increase in cardiomyocyte proliferation, and neovascularization, all of which alleviated MI. [71,72] It has also been observed that exercise-induced cardiomyocyte-derived EVs, enriched with specific miRNAs (especially miR-29b and miR-455,) regulated matrix metalloproteinase (MMP)−9, an enzyme associated with fibrosis and myocyte uncoupling. [73]…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…[70] Rats injected with cardiomyocyte-derived EVs rich in HSP20 showed activation of vascular endothelial growth factor receptor 2 and Akt signaling, a decrease in tumor necrosis factor and IL-1, an increase in cardiomyocyte proliferation, and neovascularization, all of which alleviated MI. [71,72] It has also been observed that exercise-induced cardiomyocyte-derived EVs, enriched with specific miRNAs (especially miR-29b and miR-455,) regulated matrix metalloproteinase (MMP)−9, an enzyme associated with fibrosis and myocyte uncoupling. [73]…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…With this regard, it is important to recognize that prescription of aspirin or low molecular-weight heparin is not uncommon in real-world registries [11]. In these registries, low molecular heparin is frequently employed, despite the lack of evidence, in patients with AF and active cancer, which is a setting of difficult management considering the risk of bleeding and the lack of randomized studies [3,12]. It is noteworthy that none of the scores proposed for estimating the risk of bleeding (Table 1) includes active cancer or a history of cancer, thus making any decision-making problematic.…”
mentioning
confidence: 99%